The Pregnancy, Arsenic, and Immune Response (PAIR) Study in rural northern Bangladesh. Issue 2 (9th February 2023) - Avolio, Lindsay N.; Smith, Tyler J. S.; Navas‐Acien, Ana; Kruczynski, Kate; Pisanic, Nora; Randad, Pranay R.; Detrick, Barbara; Fry, Rebecca C.; van Geen, Alexander; Goessler, Walter; Karron, Ruth A.; Klein, Sabra L.; et al.
Abstract: Background: Arsenic exposure and micronutrient deficiencies may alter immune reactivity to influenza vaccination in pregnant women, transplacental transfer of maternal antibodies to the foetus, and maternal and infant acute morbidity. Objectives: The Pregnancy, Arsenic, and Immune Response (PAIR) Study was designed to assess whether arsenic exposure and micronutrient deficiencies alter maternal and newborn immunity and acute morbidity following maternal seasonal influenza vaccination during pregnancy. Population: The PAIR Study recruited pregnant women across a large rural study area in Gaibandha District, northern Bangladesh, 2018–2019. Design: Prospective, longitudinal pregnancy and birth cohort. Methods: We conducted home visits to enrol pregnant women in the late first or early second trimester (11–17 weeks of gestational age). Women received a quadrivalent seasonal inactivated influenza vaccine at enrolment. Follow‐up included up to 13 visits between enrolment and 3 months postpartum. Arsenic was measured in drinking water and maternal urine. Micronutrient deficiencies were assessed using plasma biomarkers. Vaccine‐specific antibody titres were measured in maternal and infant serum. Weekly telephone surveillance ascertained acute morbidity symptoms in women and infants. Preliminary Results: We enrolled 784 pregnant women between October 2018 and March 2019. Of 784 women who enrolled, 736 (93.9%) delivered live births and 551 (70.3%) completed follow‐up visits to 3 months postpartum. Arsenic was detected (≥0.02 μg/L) in 99.7% of water specimens collected from participants at enrolment. The medians (interquartile ranges) of water and urinary arsenic at enrolment were 5.1 (0.5, 25.1) μg/L and 33.1 (19.6, 56.5) μg/L, respectively. Water and urinary arsenic were strongly correlated (Spearman's ⍴ = 0.72) among women with water arsenic ≥ median but weakly correlated (⍴ = 0.17) among women with water arsenic < median. Conclusions: The PAIR Study is well positioned to examine the effects of low‐moderate arsenic exposure and micronutrient deficiencies on immune outcomes in women and infants. Registration : NCT03930017.